Modelling, fabrication and characterization of graphene/polymer nanocomposites for electromagnetic interference shielding applications. (July 2021) - Anderson, Liam; Govindaraj, Premika; Ang, Andrew; Mirabedini, Azadeh; Hameed, Nishar
Abstract: The mitigation of electromagnetic pollution is becoming an increasing issue due to the proliferation and miniaturization of electronic components. Electromagnetic interference (EMI) shields must be considered to bring about electromagnetic compatibility (EMC), where analyzing the shielding effectiveness (SE) is of great importance. Graphene-enhanced polymer composite materials are recently introduced as a replacement for metal-based EMI shielding materials due to their low cost, resistance to corrosion, lightweight, versatile, and straightforward processability, as well as broad bandwidth properties compared to conventional metal-based materials. The SE can be determined from the bulk material properties, including permittivity, permeability, and conductivity, using analytical or numerical solutions to Maxwell's equations. Though, Due to the heterogeneity of graphene-based polymer composites, characterization of these values remains difficult. This article attempts to summarise and critically review the state-of-the-art progress in the fabrication and characterization of these materials. Also, this review elaborates on accurate modelling techniques based on the underlying micromechanics, e.g., percolation, electron tunnelling, agglomeration, imperfect interface, frequency-dependent nanocapacitance and electron hopping. The model is designed to predict the electromagnetic properties of the nanocomposite from the pre-determined properties of the polymer matrix and carbon-based filler. This understanding may ultimately lead to the development of graphene/polymer composites with optimized EMI shielding properties to develop emerging EMI shielding materials. This paper focuses heavily on Graphite Nanoplatelet (GnP)/Epoxy as the choice of graphene/polymer. Graphical abstract: Image, graphical abstract